Distribution and quantification of activated platelets in platelet-rich fibrin matrices. (2nd January 2022) - Sato, Atsushi; Kawabata, Hideo; Aizawa, Hachidai; Tsujino, Tetsuhiro; Isobe, Kazushige; Watanabe, Taisuke; Kitamura, Yutaka; Miron, Richard J; Kawase, Tomoyuki
Abstract: Platelet-rich fibrin (PRF) has been widely applied in regenerative therapy owing to its simple preparation protocol. To date, the original protocol for preparing leukocyte-rich (L)-PRF has been modified to produce derivatives such as advanced (A)-PRF, concentrated growth factors (CGF), and horizontal (H)-PRF. However, these derivatives have not been rigorously compared to explore possible differences. We previously developed and validated a nondestructive near-infrared (NIR) imaging method to quantitatively examine the platelet distribution in PRF matrices. To further evaluate the characteristics of platelets in PRF, we herein examined the distribution of activated platelets. Four types of PRF matrices were prepared under different centrifugal conditions from blood samples obtained from the same healthy donors. After fixation and compression, the matrices were stained immunohistochemically without sectioning and visualized using an NIR imager. Qualitative morphological analysis revealed that whole platelets were distributed widely and homogeneously in H-PRF and A-PRF, but localized along the distal tube surface in L-PRF and CGF. Activated platelets were distributed as were whole platelets in A-PRF, L-PRF, and CGF, but localized mainly in the "buffy coat" region in H-PRF. Quantitative analysis revealed that there was no significant difference in the ratio of activated to whole platelets between PRF derivatives. These findings suggest that platelet activation is similarly induced in fibrin matrices regardless of centrifugal speed or rotor angulation. However, only the H-PRF group was distinguishable from the other PRF derivatives in terms of activated platelet distribution.